Вивчення образів, міфологізованих письменниками, на уроках української літератури в 9-11 класах - Сидоренко, Юлія Олександрівна (My University, 2019)
The article deals with the peculiarities of the functioning of mythological characters in the works of Ukrainian literature, which are part of the school curriculum of 9-11 grades. It outlines a system of special skills that students need to master when processing texts with mythologized characters. The author offers special types of analysis of images mythologized by writers, with the purpose of understanding their artistic role and understanding the general concept of the author’s text. A methodical system of their study has been developed for the holistic characterization of a group of selected works: the stages of work, specially adapted variants of the figurative and conceptual-figurative analysis, techniques and types of work in the lesson. Examples of practical application of the developed analysis schemes for mythologized characters of works, taught in 9-11 grades of secondary school are presented. Educational activity is enriched by in depth elaboration of mythological elements that make the works of art relevant.
Studying of images mythologized by writers at the lessons of Ukrainian literature in 9-11 grades
Keywords: mythologized images, conceptual-figurative analysis, mythologeme, subtext of the work, artistic parallelism